In-tube Heat Transfer and Pressure Drop of HFC-134a and Ester Lubricant Mixtures in a Smooth Tube and a Micro-Fin Tube: Part I Evaporation - Eckels, Steven J.; Doerr, T.M.; Pate, M.B. (My University, 1994)
In-tube heat transfer coefficients and pressure drops during evaporation are reported for mixtures of refrigerant R134a and a penta erythritol ester mixed-acid lubricant. The ester lubricant was tested at viscosities of 169 SUS and 369 SUS over a lubricant concentration range of 0% to 5% in both a smooth tube and a micro-fin tube. The average saturation temperature used was 1 deg C (33.8 deg F). Measurements were taken for the refrigerant-lubricant mixture over a mass flux range of 85 kg/m2.s (62,700 lb/ft2Ã h) to 375 kg/m2Ã s (276,640 lb/ft2Ã h) in test tubes with an outer diameter of 9.52mm (three/eighths in.). Heat transfer coefficients during evaporation increased at low concentrations of the 169-SUS ester lubricant and then dropped off at high lubricant concentrations in both the smooth tube and the micro-fin tube. The higher viscosity 369-SUS lubricant decreased the heat transfer coefficients in both tubes over the range of lubricant concentrations tested. Pressure drops during evaporation increased in both the smooth tube and the micro-fin tube with the addition of ester lubricant viscosity. The heat transfer coefficients for the micro-fin tube were 100% to 50% higher than those for the smooth tube, with the higher values occurring at low mass fluxes. Pressure drops in the micro-fin tube were 10 to 20% higher than those in the smooth tube.
Citation:Eckels, S.J., T.M. Doer, and M.B. Pate, In-tube heat transfer and pressure drop of R-134a and Ester lubricant mixtures in a smooth tube and a micro-fin tube: Part I-Evaporation. ASHRAE Transaction, 1994. 100(2): p. 265-282
Keywords: Heat Flow; Heat Transfer Coefficient; Pressure Drop; Refrigerants; Lubricants; R134A